Coral-like amorphous carbon nanotubes synthesized by a modified arc discharge. Issue 6 (3rd June 2017) - Zhao, Tingkai; Ji, Xianglin; Jin, Wenbo; Yang, Wenbo; Li, Tiehu
ABSTRACT: A coral-like amorphous carbon nanotube was prepared by a modified arc discharging furnace in hydrogen atmosphere with a mixture of Mo-Co2 O3 -Mg powders as catalyst at 600°C. This carbon nanotube presented a microscopic coral-like by SEM observation and amorphous structure of nanotubes by HRTEM observation. The XRD diffraction and Raman pattern presented noncrystal characteristics compared to the normal graphite structure. We believed that these results may be affected by the "synergistic" effect of catalyst, atmosphere, and temperature in the synthesis process. The possible explanations to the formation mechanism of this novel carbon nanotube have also been proposed.